2017
DOI: 10.1371/journal.pone.0185364
|View full text |Cite
|
Sign up to set email alerts
|

Learning and forgetting in the jet fighter aircraft industry

Abstract: A recent strategy carried out by the aircraft industry to reduce the total cost of the new generation fighters has consisted in the development of a single airframe with different technical and operational specifications. This strategy has been designed to reduce costs in the Research, Design and Development phase with the ultimate objective of reducing the final unit price per aircraft. This is the case of the F-35 Lightning II, where three versions, with significant differences among them, are produced simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Production costs reported by Lockheed suggested that depreciation of learning was an important factor and that costs rose when the rate of production fell. Bongers (2017) finds that simultaneous production of different versions of the same aircraft accelerates forgetting. Darr et al (1995) study the depreciation of knowledge in pizza stores and conclude that learning by doing depreciates rapidly in these stores.…”
Section: Calibrationmentioning
confidence: 99%
“…Production costs reported by Lockheed suggested that depreciation of learning was an important factor and that costs rose when the rate of production fell. Bongers (2017) finds that simultaneous production of different versions of the same aircraft accelerates forgetting. Darr et al (1995) study the depreciation of knowledge in pizza stores and conclude that learning by doing depreciates rapidly in these stores.…”
Section: Calibrationmentioning
confidence: 99%
“…Thus, purchases are made to shorten the technology mastery process and minimise investment [7]. However, purchasing licenses also has weaknesses, especially during the process, because (i) not everything related to the purchased technology is transferred [11], (ii) the transferred technology may not be absorbed by all because of differences in culture, language, and knowledge [12], and (iii) the transferred technology requires maintenance to be developed [13]. Furthermore, the transferred capabilities are limited to production capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in the previous sections, the experience curve approach provides a strong analytical construct to describe and anticipate technology cost developments. The approach has also achieved overwhelming empirical evidence across many sectors, including, manufacturing [107], medical procedures [108], aerospace and defense industry [109,110], ship production [111,112], semiconductors [113,114], consumer products [115,116]; in addition to energy sector [31,43,77]. However, several limitations and uncertainties are found to distort the outcomes of the experience curve analysis.…”
Section: Uncertainties In the Experience Curve Approachmentioning
confidence: 99%